Learning Arabic Language Sciences Based on Technology in Traditional Islamic Boarding Schools in Indonesia - Nasution, Sahkholid; Asari, Hasan; Al-Rasyid, Harun; Dalimunthe, Rasyid Anwar; Rahman, Aulia (Nazhruna: Jurnal Pendidikan Islam, 2024)
This research aims to analyze traditional Islamic boarding school leaders' perceptions of technology, models of learning Arabic sciences in traditional Islamic boarding schools, forms of using technology in learning Arabic language sciences in traditional Islamic boarding schools, and foundation support for using technology in learning sciences. -Arabic language knowledge in traditional Islamic boarding schools. The type of research used is qualitative-descriptive. Research data was obtained using observation methods, in-depth interviews, and documentation. The instruments used are observation lists, interview lists, and documentation lists. Data were analyzed using ATLAS—ti9 software. The research results show that (1). traditional Islamic boarding school leaders' perception of technology is very positive, and there is no rejection of the presence of technology; (2). The model of learning Arabic language sciences in traditional Islamic boarding schools is still preserved, such as using the yellow book with the bandongan, sorogan, and wetonan methods (3). Using technology in learning Arabic language sciences in traditional Islamic boarding schools by operating computers, laptops, focus, and cell phones with the help of the internet (4). The foundation supports the use of technology in learning Arabic language sciences in traditional Islamic boarding schools by disbursing sufficient funds to procure learning technology tools or by building collaborations with other parties. This research aims to increase the use of learning technology in traditional Islamic boarding schools to create effective and efficient learning but remain resistant to Islamic boarding school values and traditions.